Effect of lymph node resection on prognosis of resectable intrahepatic cholangiocarcinoma: A systematic review and meta-analysis - Li, Feiyu; Jiang, Yong; Jiang, Liyong; Li, Qingbin; Yan, Xiangyu; Huang, Songhan; Chen, Ji; Yuan, Shuai; Fu, Yingda; Liu, Jun (Frontiers in Oncology, 2022)
Background:The purpose of this meta-analysis was to evaluate the efficact of lymph node dissection in patients with intrahepatic cholangiocarcinoma. Methods:The literatures from January 2009 to December 2021 were searched to determine the comparative study of lymph node dissection and non-lymph node dissection in ICC patients. Results:17 studies were included in the analysis. There were no significant differences in 1,3,5-year overall survival(OR 0.80 p=0.10; OR 0.93 p=0.71; OR 0.80 p=0.21) and 1,3,5-year disease-free survival(OR 0.89 p=0.73; OR 0.92 p=0.81; OR 0.85 p=0.62). Conclusions:Lymph node dissection does not seem to have a positive effect on the overall survival and disease-free survival.